Pulmonary Mucormycosis in Chronic Lymphocytic Leukemia and Neutropenia. (19th February 2018) - Mir, Izza; Basnet, Sijan; Ellsworth, David; Mohanty, Elan
Abstract : Pulmonary mucormycosis is a rare life-threatening fungal infection associated with high mortality. We present the case of a 61-year-old man with history of chronic lymphocytic leukemia who presented with fever and cough, eventually diagnosed with pulmonary mucormycosis after right lung video-assisted thoracoscopic surgery. The patient was successfully treated with amphotericin B and right lung pneumonectomy; however, he later died from left lung pneumonia.